Natural resource management (NRM) and peacebuilding in case of Liberia - Galiya M. Burakanova, Takhira A. Kamaljanova, (Opción, 2020)
The purpose of the study is to analyze conflicts caused by natural resources and how natural resource management can prevent conflict and contribute to peacebuilding as an example of one of the African countries of Liberia via comparative qualitative research method. As a result, for Liberia, it is possible to use their natural resources to attract investment and promote higher economic development. In conclusion, some recommendations will be made on how to support peacebuilding through an effective NRM.